Enhancement of fast hierarchical mobile IPv6 protocol to support macro-mobility management - Omar Zakaria (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Mobility and real-time traffic such as Voice over IP are two expanding areas within communication systems. The concept of combining these two areas contains several challenging problems. Providing real time data traffic to the real time application which cannot tolerate delay has become ever more important feature of mobile networks in recent years. Fast Hierarchal mobile IPv6 (F-HMIPv6) reduces the packet loss and improves the handover consequences in case of micro-mobility movement, by reducing the network registration time and the address resolution time. However it does not suit in case of macro mobility when the mobile node moves to different network with different MAPs (Mobility Anchor Points). More efforts are needed to support both macro and micro mobility (inter/intra domain movement). This dissertation aims to present and evaluate a new approach to support macro mobility movement. The evaluation of this proposed approach is done using simulation and analytical approach. The proposed enhancement is benchmarked with the standard Mobile IPv6 (MIPv6) and Hierarchical Mobile IPv6 (HMIPv6) which are proposed by Internet Engineering Task Force. The results obtained show that the proposed scheme has better performance than MIPv6 and HMIPv6 in term of packet loss and handover latency.